Towards a floating RMB exchange rate regime. - Bin, Zhang (China Economic Journal, 2018)
The main challenge of China’s current exchange rate regime is that with large and frequent interventions, the RMB exchange rate cannot adequately respond to the changes in economic fundamentals. This will lead to unilateral exchange rate expectations and large-scale capital inflows or outflows. In addition, large and frequent foreign exchange market interventions have a negative impact on economic structural optimisation, RMB internationalisation, and foreign investment. Two strategies can be used to introduce a floating exchange rate system: one is a free-floating exchange rate, and the other is wide range fluctuation against a basket of currencies. The latter is a transitional option before introduction of the former: a free-floating exchange rate.